Paul’s Church Leadership Style a Road Map for Christian Leaders in Nigeria - Okobia , Faith Nkem (International Journal of Culture and Religious Studies, 2024)
Purpose: This study examined Paul’s Church Leadership style a road map for Christian leaders in Nigeria, and a careful study on how Christian leaders in Nigeria lead in order to point out their weaknesses and guide them to make the future better by avoiding their mistakes by imitating Paul and Jesus Christ. Methodology: Historical method was used which enabled the researcher to trace the genesis of bad leadership to when emphasis was shifted from holiness to materialism and lack of fear of God. Primary and Secondary data collections were used such as observation, interview, books and journals. Findings: The book of Acts and the 13 books written by Paul in the New Testament provided an outstanding example of a leader with great faith, zeal, and perseverance in the face of opposition. Paul demonstrated the qualities of a good leader by fulfilling his ministry, evangelizing the Gentile world, and preaching sound doctrine. He developed by mentoring his successors and delegated responsibility to them for them to develop their potentials Unique Contribution to Theory, Practice and Policy: Christian leaders should lead like Paul by constantly imitating Christ, and they should allow the Holy Spirit to guide them to avoid mistakes. They should also train their successors and ensure they are called by God before taking leadership positions. This study had also exposed the weaknesses of bad leaders for them to change to avoid conflict in the church and for their members not to go astray.